Case Report: A long-term survival case of diffuse large B-cell lymphoma with left ventricular infiltration and spinal cord compression - Sun, Rui; Jin, Chenxing; Qin, Henan; Zhang, Wenhe; Ning, Zhen; Liu, Jiwei; Wang, Aman (Frontiers in Cardiovascular Medicine, 2023)
Background Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma and may occur with lymph node and/or extranodal involvement. However, DLBCL with intracardiac mass is exceedingly rare. In the reported literature, the intracardiac infiltration of DLBCL mostly involves the right ventricle. Lymphoma that invades the heart has an aggressive nature, with symptoms that are easily ignored initially and can lead to multiple complications in severe cases, resulting in a poor prognosis. Early screening and diagnosis may significantly improve the survival rate. Early diagnosis may significantly improve outcomes. Case summary We presented a 68-year-old woman with back pain. PET/CT suggested increased FDG metabolism in the left ventricle, right adrenal gland, right erector spinae intramuscularis, multiple bones and multiple lymph nodes. Contrast-enhanced ultrasound showed a left ventricular apical mass with ventricular septum thickening. Cardiac MRI suggested a 1.6*1.1*2.1 cm mass in the apical-central portion of the left ventricle. Biopsy of the right neck mass confirmed the pathologic diagnosis of diffuse large B-cell lymphoma. However, before the pathologic diagnosis was confirmed, the patient was paralyzed due to spinal cord compression caused by the progression of bone metastases. Subsequently, pathology confirmed the diagnosis of diffuse large B-cell lymphoma, and rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) was treated immediately as first-line therapy. In addition, glucocorticoids and mannitol dehydration were administered to relieve the symptoms of spinal cord compression. After 8 cycles of R-CHOP, the tumor at all sites had almost complete regression. The patient was able to walk normally and had no tumor-related symptoms. Conclusions We present a case of DLBCL with a very high tumor load that involved multiple organs, including the left ventricle, but exhibited no cardiac-related symptoms. The combination of various imaging modalities is valuable for the diagnosis of cardiac infiltration. The mass in the left ventricle almost completely regressed after R-CHOP treatment, and no recurrence has occurred in the 5 years of follow-up so far.